Earnings management e securitização de ativos por empresas estrangeiras listadas na NYSE - Luciana Alves Rodrigues (2011)
SFAS 140 requires companies that have securitized financial assets report their accounting policies, volume, cash flow, principal assumptions used to determine the fair value of retained interests and sensitivity analysis of the fair value by changing the main premises. The securitization accounting operations as well as estimates of fair value has been the subject of international research. In this sense, it is estimated that this is a topic of high relevance in the national financial landscape. Therefore, this study aimed to identify whether the general managers of foreign companies listed on the NYSE performing securitization practice Income Smoothing. We sought specifically to describe the securitization operations carried out by member firms of the sample and compare the results with the results presented by DMS (2010), regarding the relationship between securitization gains and discount rates and the relationship between securitization gains and incentives to manage results, also apply metrics Eckel (1981) for detecting the presence of smoothing the companies analyzed. So, we carried out a descriptive, bibliographical and documentary research with a quantitative approach, using the 20F or 40F forms of foreign companies that have shares listed on the NYSE in the period from 2007 to 2010. The sample consisted of 80 companies, among which 16 had the basic information needed to implement the model proposed by DMS (2010) to analyze the relationship between earnings and the practice of securitization Earnings Management. The results of qualitative analysis showed that most companies conduct operations through the securitization SPE/Trust, in order to achieve diversification of funding sources and greater liquidity. Application of the model proposed by DMS (2010) expected the negative relationship between the dependent variable "Securitization Gain" and the explanatory variables "Result Pre-securitization" and " Result Pre-securitization" was not confirmed in any of the regressions estimated. Among the proxies added to the regressions to isolate the discretionary component of the gain, the variable Indust_Gains presented explanatory power of the dependent variable, presenting with expected sign and statistically significant at 5% in almost all regressions tested. Before the analyzes and the results verified that the model proposed by DMS (2010) was not effective to detect the presence or absence of smoothing, namely, the results were not sufficient to provide evidence companies that trade their shares on the NYSE using the flexibility available in the rules of fair value accounting to manage revenues from securitization. The application of metric Eckel (1981), despite having been identified evidence of income smoothing in 50% of companies surveyed, one can not say that this phenomenon is due to the smoothing of revenue securitization, since the metric used is limited to indicate only the presence or absence of smoothing results without identifying its source.